Analisis Strategi Pemasaran Perusahaan Apple Dalam Meningkatkan Pemasaran Global - Fidella Damayanti; Kezia Rostiana (Pusat Riset dan Inovasi Nasional, 2024)
Apple Inc. is a multinational technology company headquartered in Cupertino, California. In April 1976 the Apple Company was founded by Steve Jobs, Steve Wozniak, and Ronald Wayne. The company designs, develops and sells electronic goods, software and online services. Software produced by Apple includes the macOS and iOS operating systems, the iTunes media player, the Safari web browser, iLife and iWork creativity and productivity tools, as well as many professional applications such as Final Cut Pro, Logic Pro, and Xcode. The Apple company focuses on brand value and uniqueness through product quality, both in design, function and technological systems. Apple then implemented a branding strategy for its brand by presenting it as a manufacturer of technologically advanced and user-friendly devices. Another thing that the Apple company does is focus on products and user experience by creating connectivity between gadgets and their properties so that they can only use Apple products and cannot use other brand products. That's why Apple creates products and services that are designed to be inclusive from the start, with built-in accessibility features to help you connect, create, and do the things you want. Love in the way that suits you best. Therefore, Apple Company designs every product to keep your data safe and protected. The marketing strategy carried out is to provide brand value and uniqueness through the quality of the product, both in terms of design, features and the technology system in it. Apart from that, the Apple brand is unique in its elegant logo design with the shape of a bitten apple logo. The Apple company also always innovates by releasing its newest products.